Odpowiedź :
Odpowiedź:
zad 4
a)12(x + 3) -5(4 - 3x)=12x+36-20+15x=27x+16
b) -7a(2a + b) - 3b(2 + 3a)=-14a²-7ab-6b-9ab=-14a²-16ab-6b
c) 5m(m - 2) + 3n(2 - n)=5m²-10m+6n-3n²
zad 3
a)) -5(2x - 7)=-10x+35
b) 2a(3ab - 5b)=6a²b-10ab
c) 11m(3 + 3n)=33m+33mn
d)x(3x+5x²)=3x²+5x³
Szczegółowe wyjaśnienie:
Zadanie 4
a)
12(x + 3) - 5(4 - 3x) = 12x +36 - 20 + 15x = 27x + 16
b)
-7a(2a + b) - 3b(2 + 3a) = -14a² - 7ab - 6b - 9ab = -14a² - 16ab - 6b
c)
5m(m - 2) + 3n(2 - n) = 5m² - 10m + 6n - 3n²
Zadanie 3
a)
-5(2x - 7) = -10x + 35
b)
2a(3ab - 5b) = 6a²b - 10ab
c)
11m(3 + 3n) = 33m + 33mn
d)
x(3x +5x²)= 3x² + 5x³